2016
DOI: 10.1136/bmjopen-2016-011558
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and mortality in prehospital emergency patients transported to hospital: a population-based and registry-based cohort study

Abstract: ObjectiveKnowledge about patients after calling for an ambulance is limited to subgroups, such as patients with cardiac arrest, myocardial infarction, trauma and stroke, while population-based studies including all diagnoses are few. We examined the diagnostic pattern and mortality among all patients brought to hospital by ambulance after emergency calls.DesignRegistry-based cohort study.Setting and participantsWe included patients brought to hospital in an ambulance dispatched after emergency calls during 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 19 publications
10
70
2
Order By: Relevance
“…Women more often than men contacted OOH-PC, and a considerable part of calls to OOH-PC concerned children [29][30][31][32]. Two Danish studies on EMS contacts reported similar percentages of calls made by women, but these studies found a slightly lower mean age than found in our study [33,34]. This difference is likely to be due to our stratification into groups (children and adults) and exclusion of patients aged 13-18 years.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 69%
“…Women more often than men contacted OOH-PC, and a considerable part of calls to OOH-PC concerned children [29][30][31][32]. Two Danish studies on EMS contacts reported similar percentages of calls made by women, but these studies found a slightly lower mean age than found in our study [33,34]. This difference is likely to be due to our stratification into groups (children and adults) and exclusion of patients aged 13-18 years.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 69%
“…23 The diagnoses comprising the calculation of the CCI are all extracted from admission at hospitals or outpatient treatments at hospitals. Thus, treatments administered at the general practitioners are not routinely collected at the National Patient register.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In 2006 the North Denmark Region was the rst to implement an electronic prehospital medical record (amPHI ®). The patient data are accessible for the healthcare staff at the EMCC and incorporated into the hospitals' electronic medical record [3].…”
Section: Study Settingmentioning
confidence: 99%
“…However, actual knowledge about the disease pattern in patients attended by emergency ambulances is scarce, due to limited prehospital patient data. In the North Denmark Region, we established a linkage between patient data from ambulance runs and hospital diagnoses [3], examining patients brought to the hospital by ambulance after calling the national emergency number 112. The two non-speci c diagnostic groups, R ('symptoms, signs and abnormal clinical and laboratory ndings, not elsewhere classi ed') and Z ('factors in uencing health status and contact with health services') in the International Classi cation of Diseases, 10 th edition (ICD-10) [4], together constituted one-third of the hospital diagnoses given to the included patients [3].…”
Section: Introductionmentioning
confidence: 99%